Motivasi Peserta Outbound Dalam Mengikuti Kegiatan Olahraga Rekreasi Di TSOT (The Survival Outbound Team) Pasuruan - Lulus Endira Fisnaviola Rengganis; Pudjijuniarto Pudjijuniarto; Ratna Candra Dewi; Muhammad Dzul Fikri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Motivation plays an important role in directing one's behavior in carrying out activities. The existence of motivation can arouse a person's enthusiasm to increase commitment to practice, with the aim of achieving the best results and fulfilling their own desires. The purpose of this study was to determine the level of motivation of participants in participating in recreational sports activities at TSOT Outbound. This study uses descriptive research with survey methods. In this study, researchers used Ramdom sampling technique randomly with a sample of 20% of the population, so that the number of respondents taken was 30 respondents from a population of 150 participants. The results of this study indicate the average calculation for each type of motivation that intrinsic motivation consists of, the indicator of the benefits of exercising of 74.44% in the high category, the indicator of maintaining health of 82.08% in the very high category, the indicator of satisfaction exercising 77.5% in the high category, the indicator of relieving boredom of 72.5% in the high category, with a total total of 76.78% of intrinsic motivation. While extrinsic indicators consist of, friendship indicators 80.83% in the high category, location indicators 70.58% in the high category, cost indicators 73.33% in the high category, and weather indicators 71.04% in the high category, with a total amount of extrinsic motivation of 74.03%.